The effects of preparation period exercises on the hematological parameters of the taekwondo athletes - E. Boyalı; T. Sevindi; M.F. Yüksel; H. Demir (Physical Education of Students)
Purpose: This study aimed at examining the effects of preparation period exercises, which were applied for eight weeks to elite level taekwondo athletes, on the hematological parameters. Material: Totally 21 athletes with international degrees from the university taekwondo team participated in this study, 12 of whom were female (Mean age: 20.3 - Mean exercise age: 8.8) and 9 of whom were male athletes (Mean age: 20.3 - Mean exercise age: 9.5). The participants attended an 8-week exercise program for 5 days a week, which included basic motoric features and technical and tactical development. 4 cc blood samples were taken from the right antecubital vein before and after the preparation period exercises. On the blood samples, WBC, GRAN, GRAN %, LYM, LYM %, MID and MID % values were examined among leukocyte sub-groups; RBC, HGB, HCT, MCV, MCH, MCHC and RDWC values were examined among the erythrocyte sub-groups, and PLT, MPV, PCT and PDW values were examined among thrombocyte sub-groups. Results: At the end of the study, we determined that there was a statistically significant increase in the MCHC values of both the male and the female taekwondo athletes. Moreover, it was determined that there were statistically significant decreases in the HCT, MCV, MCH, MPV and PCT values of the female taekwondo athletes, and in the MCV, MPV and PCT values of the male taekwondo athletes. Conclusions: As a conclusion, we can state that the 8-week exercises applied during the preparation period affected the hematological parameters of the male and female taekwondo athletes to an extent, however, this effect was limited and it did not cause an important change.